Future/memory : street culture and contemporary art /. - Osterholt, Manuel; Europaisches Zentrum der Kunste Dresden (Hellerau, Germany) (Sweden : Dokument Press, 2013)
Boogie ; Martha Cooper ; Horfee ; Cody Hudson ; HuskMitNavn ; Cleon Peterson ; Jay "One" Ramier ; Skki(c) ; SuperBlast
Published to accompany the exhibition held at HELLERAU - European Center for the Arts Dresden, Summer 2013.
boek
Keywords: Street art -- Exhibitions; City and town life in art -- Exhibitions